TOURISM DESTINATION COMPETITIVENESS MODEL FOR THE CITY OF SOLO - Dian Deliana; Final Prajnanta (Journal of Social and Economics Research, 2023)
This study aims to identify the main factors that affect the competitiveness of tourist destinations in the city of Solo, involving an analysis of aspects of cultural uniqueness, service standards, and tourism infrastructure. This study used the descriptive-qualitative method. The results show First, the cultural uniqueness and heritage of the City of Solo appear to be major factors in attracting tourists. Traditional art, local cuisine, classic architecture, and cultural celebrations are the main attractions that set this destination apart. Second, superior service quality is proven to have a key role in creating a positive experience for tourists. Being responsive to their needs creates an emotional bond that encourages return visits and recommendations to others. Third, the influence of technology and social media in the paradigm of seeking information and planning travel has undergone changes. The use of technology, such as an augmented reality-based guide application, creates an interactive experience that enriches the visit.